The Impact of Sleep Patterns, Nap Policy, and Stress Levels on Elementary School Students' Academic Achievement in China - Muh Ibnu Sholeh; Himad Ali; Sokip Sokip; Asrop Syafii; Sulistyorini Sulistyorini; Imam Fuadi; Nur Azah; Munif Munif; Mochammad Syafiuddin Shobirin; Sahri Sahri (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study aims to investigate the relationship between students' sleep patterns, nap policies, and stress levels, as well as their impact on academic achievement. The research employs a quantitative method with an observational design, involving 500 students and 50 teachers from five elementary schools in Guangdong Province. The research instrument consists of a validated questionnaire assessed using a Likert scale. Data analysis was conducted using descriptive techniques, linear regression, and multiple regression analysis with SPSS version 25. The findings indicate that students' sleep patterns (SSP) have a positive and significant relationship with academic achievement, with a regression coefficient of 0.42 (SE = 0.08, t = 5.25, p < 0.001). The nap policy (NP) also shows a positive and significant correlation with student achievement, with a regression coefficient of 0.62 (t = 12.45, p < 0.001). Conversely, students' stress levels (SSL) exhibit a negative and significant relationship with academic achievement, with a regression coefficient of -0.35 (t = -8.25, p < 0.001). Collectively, these three variables have a significant impact on student achievement, with regression coefficients of 0.35 for sleep patterns, 0.52 for nap policies, and -0.25 for stress levels (p < 0.001). This study has limitations, including a sample restricted to a single province and an observational approach that does not fully capture causality. The study's implications for elementary education policy highlight the importance of adjusting school schedules to support healthy sleep patterns and implementing structured nap policies to optimize student achievement. Additionally, interventions to reduce academic stress should be considered to foster a more conducive learning environment.